Management of pediatric mandibular fractures using bioresorbable plating system – Efficacy, stability, and clinical outcomes: Our experiences and literature review - Mahinder Singh; R.K. Singh; Deepak Passi; Mohit Aggarwal; Guneet Kaur (Journal of Oral Biology and Craniofacial Research)
Aims: The purpose of this study was to determine the efficacy and stability of the biodegradable fixation system for treatment of mandible fractures in pediatric patients by measuring the bite force. Methods: Sixty pediatric patients with mandibular fractures (36 males, 24 females) were included in this study. The 2.5-mm resorbable plates were adapted along Champy's line of ideal osteosynthesis and secured with four 2.5 mm diameter monocortical resorbable screws, 8 mm in length. All patients were followed for 10 months. Clinical parameters, such as soft tissue infection, nonunion, malunion, implant exposure, malocclusion, nerve injury, and bite force for stability, were prospectively assessed. Results: Adequate fixation and primary bone healing was achieved in 100% of the cases. Six minor complications (10%) were observed: 2 soft tissue infections (3%), 1 plate dehiscence (2%), 1 malocclusion (2%), and 2 paresthesia (3%). Conclusion: 2.5-mm resorbable plating system along Champy's line of ideal osteosynthesis is a good treatment modality for mandible fractures in pediatric patients.